INDICATORS OF FORMALIZED DESCRIPTION QUALITY AND ANALYSIS OF PRODUCTION TECHNOLOGIES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
This paper discusses conceptual basis for assessment and analysis of model quality relating to formalized description of technologies. The authors give indicators used to assess formalized and textual descriptions of technologies. They raise some questions concerning the analysis of technologies that enable to make a list of indicators. The paper examines decomposition structures of specific technologies and provides the calculations of introduced coefficients.